The Ulama’s Classical Works in Six Pesantren in Bandung, West Java, Indonesia - Zulkarnain Yani; Ahmad Hakam (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2021)
Ulama have a big role in the life of a plural society. In their efforts, achievements in education, politics, socio-economy, and others have been completed. These attainments were not separate from the role of ulama or kyai who wrote books or kitab to be used as teaching materials in Islamic boarding schools, pesantren, or religious assembly, teaching, in the community. This research uses a descriptive qualitative approach and data were collected using documentation studies and interviews. This study was conducted in six pesantren in Bandung. There are 39 works of the pesantren ulama with various studies such as Islamic jurisprudence, Sufism, theology, Arabic grammar, hadith, Arabic morphology, astronomy, and Sufi path. The results are hoped to enrich the knowledge and literature about the various works of pesantren ulama in Bandung area from the 19th – 20th century which have not been known by the public so far and to give characteristic that is specific to the knowledge in the pesantren. In addition, this article can be an entry point for other researchers to conduct a more in-depth study of the contents of the ulama’s works.